Impact of Co-occurring Mental Disorders and Chronic Physical Illnesses on Frequency of Emergency Department Use and Hospitalization for Mental Health Reasons - Gentil, Lia; Grenier, Guy; Meng, Xiangfei; Fleury, Marie-Josée (Frontiers in Psychiatry, 2021)
Background: Patients with mental disorders are at high risk for a wide range of chronic physical illnesses (CPI), often resulting in greater use of acute care services. This study estimated risk of emergency department (ED) use and hospitalization for mental health reasons among 678 patients with mental disorders and CPI compared to 1,999 patients with mental disorders only. Methods: Patients visiting one of six Quebec (Canada) ED for mental health reasons and at onset of a mental disorder in 2014-15 (index year) were included. Negative binomial models comparing the two groups estimated risk of ED use and hospitalization at 12-month follow-up to index ED visit, controlling for clinical, sociodemographic, and service use variables. Results: Patients with mental disorders, more severe overall clinical conditions and those who received more intensive specialized mental health care had higher risks of frequent ED use and hospitalization. Continuity of medical care protected against both ED use and hospitalization, while general practitioner consultations protected against hospitalization only. Patients aged 65+ had lower risk of ED use, whereas risk of hospitalization was higher for the 45-64 versus 12-24- year age groups, and for men versus women. Conclusion: Strategies including assertive community treatment, intensive case management, integrated co-occurring treatment, home treatment and shared care may improve adequacy of care for patients with mental disorders-CPI, as well as those with mental disorders only whose clinical profiles were severe. Prevention and outreach strategies may also be promoted, especially among men and older age groups.